Bumble: Swipe Right for your Prince Charming: New Literacy Practice (Iris Journal of Scholarship)
With the prevalence of online dating at an all time high, the phrases "swipe right" or "swipe left" have become indicative of something much more than their intended purpose. I chose to analyze my own experience with Bumble as a part of a "new literacy practice" with the original intent to present my research as an assignment for class. This experiment quickly morphed into an investigation of my self-perception and of the power and agency, or lack thereof, in the application.